'Despite the special bonds that tie us': Portugal, Brazil, and the South Atlantic in the late Cold War. Issue 3 (3rd July 2021) - Seabra, Pedro
ABSTRACT: As the Cold War entered the mid-1980s, concerns over the Brazilian nuclear programme lingered on through the global stage. In this context, Brazil's 1986 proposal for a Zone of Peace and Cooperation in the South Atlantic (ZOPACAS) emerged as an opportunity to recast the country's external profile; yet, unexpected reservations emerged from the unlikeliest of its partners, Portugal. This article argues that while Portugal's initial positioning was fuelled by broader Western concerns, including misperceptions over Brazil's nuclear ambitions, the official predisposition towards such a project eventually shifted, following changes in Portugal, the region, and the world.